Violence and modernism: Ibsen, Joyce, and Woolf - Johnsen, William A. (University Press of Florida, 2003)
"A unique and important book. Our understanding of literary modernism, which we think we know so well, is transformed by these analyses of the anthropological insights that it holds for readers."--Andrew J. McKenna, Loyola UniversityEmploying Northrop Frye and Ren Girard as his theoretical foundation, Johnsen reinterprets the works of three canonical modernists--Ibsen, Joyce, and Woolf--to argue for their commitment to analyzing collective violence as a defining motive in literary modernism